An Optimization Model of the European Natural Gas System - Skarakis, Alexios; Dagoumas, Athanasios (International Journal of Energy Economics and Policy, 2017)
The European Commission has identified the Energy Union, as one of its major priorities. This aims to deliver secure, climate-friendly and affordable energy to the European citizens. Towards implementing those goals, the European Commission is working towards diversifying routes and resources, and implementing the target model for the gas and electricity markets. This paper presents an optimization model of the European natural gas system. The model identifies the natural gas suppliers’ mix for Europe and for each Member State. The model, being an optimization model, provides the economically optimum energy mix, subject to the technical and policy constraints of the gas transmission system. The model can also provide useful insights to the decision makers and market participants on the needed critical infrastructure. Model results show that the Russian natural gas is expected to have a prominent role in the EU, even by imposing energy security constraints. The incorporation in the model of the strategy of the companies, as well as the reserved capacity in the interconnections in each member state, would provide a more robust identification of the energy mix, the wholesale prices and the needed infrastructure. Keywords: Natural Gas; Optimization; pipelines; Europe. JEL Classifications: Q4; C61; L95